Analysis of Copper Sleeve Magnetic Coupling Operation Characteristic and Design of Heat Dissipation Structure - Ge Yanjun; Zhang Jun; Jiang Hao; Wang Xue; Wan Zongwei (Jixie chuandong)
The magnetic coupler produces eddy current in the conductor by permanent magnet magnetic field to realize the transmission of torque and rotational speed,while the eddy current loss will lead to permanent magnet temperature rising. When the temperature is higher than the temperature of the permanent magnet demagnetization,it will lead to irreversible permanent magnet demagnetization and magnetic coupling loss of working ability. An outer rotor is designed to be the magnetic coupling of the rotor of the inner rotor. The relation among the output speed,the torque and the coupling length is obtained by using ANSYS for electromagnetic simulation analysis. Based on the theoretical analysis and simulation calculation,the number of magnet and air gap length on the influence of the eddy current loss is also verified,and a including heat dissipation fin and heat dissipation structure of centrifugal fan is devised. By analyzing the Flow Simulation,the heat dissipation effect of the heat dissipation structure on the magnetic coupling can be verified,and the permanent magnet can be stabilized and operated in the long term.